1990
DOI: 10.1111/j.1476-5381.1990.tb14122.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the existence of ‘atypical’β‐adrenoceptors (β3‐adrenoceptors) mediating relaxation in the rat distal colon in vitro

Abstract: Responses to BRL 37344 in the presence of phentolamine (1puM) and propranolol (1 pM) were antagonized by (±)-cyanopindolol (IpM), with an apparent pA2 value of 6.67. Responses to isoprenaline, under the same conditions, were antagonized in a competitive manner by (±)-cyanopindolol (0.1 to 10pM), with the slope of the Schild plot close to unity and a pA2 value of 7.12. 6 The resistance of the relaxant responses to antagonism by phentolamine and propranolol, along with the relatively high potency of the #3-adren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
79
2

Year Published

1991
1991
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(99 citation statements)
references
References 24 publications
18
79
2
Order By: Relevance
“…The pKB of 6.3, calculated from the single (1 pM) concentration of propranolol, is low compared with 8.2-8.8 for classical f1-adrenoceptors mediating atrial stimulation and 8.3-8.6 for #2-adrenoceptors mediating tracheal relaxation suggesting an action at atypical aadrenoceptors. A similarly low pKB was reported for propranolol at atypical fl-adrenoceptors mediating lipolysis (6.6, Wilson et al, 1984) or relaxation in rat distal colon (6.57, McLaughlin & MacDonald, 1990b).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The pKB of 6.3, calculated from the single (1 pM) concentration of propranolol, is low compared with 8.2-8.8 for classical f1-adrenoceptors mediating atrial stimulation and 8.3-8.6 for #2-adrenoceptors mediating tracheal relaxation suggesting an action at atypical aadrenoceptors. A similarly low pKB was reported for propranolol at atypical fl-adrenoceptors mediating lipolysis (6.6, Wilson et al, 1984) or relaxation in rat distal colon (6.57, McLaughlin & MacDonald, 1990b).…”
Section: Discussionmentioning
confidence: 89%
“…However, relaxant responses to catecholamines which are resistant to blockade by a-and f-adrenoceptor antagonists have also been reported in a number of gastrointestinal smooth muscle preparations including rabbit stomach (Bristow et al, 1970), rabbit colon (Gillespie & Khoyi, 1977), rat oesophageal smooth muscle (Buckner & Christopherson, 1974), guinea-pig ileum (Wikberg, 1977;Bond et al, 1986;Bond & Clarke, 1987), dog colon (Grivegnee et al, 1984), rat gastric fundus (Dettmar et al, 1986;McLaughlin & MacDonald, 1990a;, rat proximal colon (Croci et al, 1988;Manara et al, 1989;Bianchetti & Manara, 1990), rabbit jejunum (Norman & Leathard, 1990), rat jejunum (Van der Vliet et al, 1990) and rat distal colon (McLaughlin & MacDonald, 1989;1990b). In the guinea-pig ileum, the order and relative potency of catecholamines is consistent with /3-adrenoceptors although responses were resistant to propranolol (Bond & Clarke, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bond & Clarke (1988) further experiments to analyse these small shifts further but it seems likely that they were produced by blockade of classical P-adrenoceptors since (i) propranolol itself has been shown to produce similar shifts in rat colon and fundus (McLaughlin & MacDonald, 1990; and (ii) o-adrenoceptor mediated inhibitory effects in smooth muscle involve abolition of spontaneous spike discharge and hyperpolarization (Bulbring, 1954;1957) and are not seen if the tissue is depolarized sufficiently to block spike generation (Magaribuchi & Kuriyama, 1972). The relative potencies of the catecholamines and BRL 37344 in the presence of prazosin and propranolol, with BRL 37344 becoming more potent than isoprenaline, are similar to those obtained by Bond & Clarke (1988) at the atypical P-adrenoceptors in guinea-pig ileum.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that the non-selective P-adrenoceptor antagonist, cyanopindolol (Engel et al, 1981) is a competitive and relatively potent antagonist at atypical P-adrenoceptors in the gut (Blue et al, 1989;McLaughlin & MacDonald, 1990; and therefore the effect of cyanopindolol on responses to adrenaline was investigated.…”
Section: Introductionmentioning
confidence: 99%